Kedudukan Kompetensi Penyusun dalam Penyusunan Analisis Mengenai Dampak Lingkungan - Putu Alex Virdana Putra; I Gusti Ngurah Dharma Laksana (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This writing has the aim of knowing the Procedures and Requirements to receive a certificate of competence in the preparation of environmental impact analysis. This is very useful, because it will provide illustrations to other people and legal entities who want to be completed if they want to have a certificate of competence in compiling an analysis of environmental impacts. With the explanation of the mechanism and requirements, therefore a person or legal entity can prepare an analysis of environmental impacts by obtaining a certificate of competence for compiling an analysis of environmental impacts. The main objective of the Environmental Impact Analysis is to ensure that business and development activities can run continuously without destroying and damaging the environment, so in another sense, business or appropriate actions from the perspective of environmental aspects.